The Development Prospects of the Chinese Economy (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The Chinese economy has become one of the most important and fastest-growing parts of the global economy in the 21st century. This article analyzes the development prospects of the Chinese economy, its growth model based on technological innovations, and the process of global integration. China's "Made in China 2025" strategy, "Belt and Road Initiative," and the policy of expanding the domestic market are aimed at strengthening its position in the global economy. However, alongside China's economic development, social inequality, environmental problems, and political conflicts in international relations also pose risks. The article examines the main directions of China's economic development, the obstacles to their implementation, and China's future strategies.